Clinical applications of SPECT-CT - Biersack, Hans-Jurgen; Ahmadzadehfar, Hojjat (Springer Berlin Heidelberg, 2014)
SPECT/CT cameras have considerably improved diagnostic accuracy in recent years. Such cameras allow direct correlation of anatomic and functional information, resulting in better localization and definition of scintigraphic findings. In addition to this anatomic referencing, CT coregistration provides superior quantification of radiotracer uptake based on the attenuation correction capabilities of CT. Useful applications of SPECT/CT have been identified not only in oncology but also in other specialties such as orthopedics and cardiology. This book covers the full spectrum of clinical applications of SPECT/CT in diagnosis and therapy planning of benign and malignant diseases. Opening chapters discuss the technology and physics of SPECT/CT and its use for dosimetry. The role of SPECT/CT in the imaging of a range of pathologic conditions is then addressed in detail. Applications covered include, among others, imaging of the thyroid, bone, and lungs, imaging of neuroendocrine tumors, cardiac scintigraphy, and sentinel node scintigraphy. Individual chapters are also devoted to therapy planning in selective internal radiation therapy of liver tumors and bremsstrahlung SPECT/CT. Readers will find this book to be an essential and up-to-date source of information on this invaluable hybrid imaging technique.